Robusta Coffee Marketing Efficiency in Magetan Regency, East Java Province - Setyowati, Setyowati; Rahayu, Endang Siti; Irianto, Heru; Handayani, Sugiharti Mulya; Sundari, Mei Tri; Widadie, Fanny (SOCA: Jurnal Sosial Ekonomi Pertanian, 2025)
Magetan Regency is one of the producers of robusta coffee known for its strong flavor and aroma, making it highly promising for export markets. However, marketing efforts and farmer interest remain low, primarily due to the perennial nature of the plant, which is perceived as less favorable for rapid capital turnover. Therefore, this study aims to assess the marketing efficiency of robusta coffee in Magetan so that farm-gate prices can become more attractive and competitive in export markets. The study employed a descriptive method with a survey research technique. A purposive method was used to determine the research location, as Magetan is recognized for producing high-quality and diverse coffee varieties. Panekan and Poncol sub-districts were selected due to their status as the largest coffee-producing areas. Farmer respondents were selected using purposive sampling, consisting of coffee farmers from two farmer groups in the respective sub-districts, where all members cultivate coffee. The snowball sampling method was employed to identify institutions involved in the marketing channels. The findings reveal that the coffee marketing institutions in Magetan Regency consist of farmers, collecting traders, retail traders, and out-of-town traders. The marketing pattern of robusta coffee in the region is categorized into three distinct channels. Overall, the marketing system for robusta coffee remains inefficient. However, Marketing Channel II has been identified as the most efficient and thus holds potential for entering export markets.